Ginsenosides, potential TMPRSS2 inhibitors, a trade-off between the therapeutic combination for anti-PD-1 immunotherapy and the treatment of COVID-19 infection of LUAD patients - Meng, Mei; Gao, Rui; Liu, Zixue; Liu, Fengxiang; Du, Shiyu; Song, Yizhi; He, Jian (Frontiers in Pharmacology, 2023)
Background: TMPRSS2 has become a target for the prevention and treatment of COVID-19 infection. Also, TMPRSS2 presented biological functions in cancer, but the roles remain controversial and the mechanism remains unelucidated. Some chemicals were reported as inhibitors of TMPRSS2 and also demonstrated other pharmacological properties. So it is important to discover more new compounds targeting TMPRSS2 for the prevention and treatment of COVID-19 infection. Methods: We analyzed the correlation between TMPRSS2 expression, methylation level, overall survival rate, and clinical parameters, and determined the correlation between TMPRSS2 and TILs in the tumor and normal adjacent tissue of LUAD and LUSC respectively. Moreover, we determined the correlation between TMPRSS2 protein level and the prognosis of LUAD and LUSC cohorts by immunohistochemistry assay. Furthermore, the TCIA database was used to predict the relationship between the expression of TMPRSS2 and response to PD-1 blocker immunotherapy in lung cancer patients. Finally, the putative binding site of Ginsenosides bound to TMPRSS2 protein was built from homology modeling to screen high-potency TMPRSS2 inhibitors. Results: We found that TMPRSS2 recruits various types of immunocytes, including CD8+, CD4+ T cells, B cells and DCs both in LUAD and LUSC patients, and the correlation between TMPRSS2 expression and CD8+ and CD4+ T cells are stronger in LUAD, but excludes macrophages and neutrophils in LUAD patient cohorts. These might be the reason that higher mRNA and protein levels of TMPRSS2 are associated with better prognosis in LUAD cohorts rather than in LUSC cohorts. Furthermore, we found that TMPRSS2 was positively correlated with the prognosis in patient nonresponse to anti-PD-1 therapy. Finally, five ginsenosides candidates with high inhibition potency were screened from the natural chemical library to be used as TMPRSS2 inhibitors. Conclusions: All these may imply that TMPRSS2 might be a novel prognostic biomarker and serve as a potential immunomodulator target of immunotherapy combination therapies of nonresponse to anti-PD-1 therapy LUAD patients. Also, these findings may suggest we should pay more attention to LUAD patients, especially those infected with COVID-19, who should avoid medicating TMPRSS2 inhibitors, such as ginsenosides to gain prophylactic and therapeutic benefits against COVID-19.